Hamzah Fansuri; The Journey of Knowledge and Religious Spiritual Works - Hudallah; Rifqi (Penerbit Hellow Pustaka, 2025)
Exploring the history of Islamic archipelago cannot be denied the influences of the ulama at that time, as well as geographical location. For the most part, even historians agree that Islam entered the archipelago via mainland Sumatra. Sumatra, as the initial foothold of Islam in the archipelago, made it a city of Islamic civilization, as evidenced by the development of Islam and the establishment of Islamic kingdoms such as the kingdom of Aceh Darussalam. So does Sumatra have any influential figures? The answer is yes, one of the phenomenal figures/ulamas who is influential is Hamzah Fansuri. This cleric is well-known and respected, apart from being known for his wahdatul wujud, he is also skilled in poetry, and has mastered Islamic teachings. It is not without reason why Hamzah Fansuri really masters poetry. Because if you look at socio-cultural conditions, people at that time were still blind/didn't know about Islam. Apart from that, the development of Islam is still synonymous with the use of poetry as poetry has become an inherent culture among the Middle East. While the Sufi's teachings of Sufism are still hotly debated, his role and position as a spiritual and religious figure will also remain debated. Likewise his contribution to Malay language, culture and literature. As the title suggests, this paper will discuss his life history and works, especially those related to hadith.